Sodium Alginate from Padina australis Modulates Innate Immune and Immune Gene Expression in Red Tilapia (Oreochromis sp.) - Toni Kuswoyo; Alim Isnansetyo; Muwantoko Murwantoko; Amir Husni; Indah Istiqomah (Faculty of Fisheries and Marine Universitas Airlangga, 2023)
Highlight Research Development of immunostimulant from natural sources is a promising approach to improve the immune status of fish Dietary administration of sodium alginate from Padina australis at 2.0 g/kg was an effective immunostimulant for red tilapia Red tilapia fed diet with sodium alginate significantly increased innate immune responses of TLC, PA, respiratory burst, SOD, TPP, lysozyme, and ACH50 activity Red tilapia fed diet with sodium alginate significantly modulated immune genes expression of GPx, TNF-α, IFN-Î³, IL-10, TGF-β1, and Hepcidin Abstract The study of immunostimulant derived from natural sources has received considerable attention in recent years. Indonesian coasts have various sources of immunostimulant, especially brown algae, which are rich in alginate. This research investigated innate immune response and immune genes in red tilapia (Oreochromis sp.) after being fed diets supplemented with sodium alginates (SA) from a brown alga, Padina australis, originating from Awur Bay, Jepara, Indonesia. This work provided comprehensive information regarding the interaction of cellular-humoral immunity and immune gene expression. Red tilapia was fed with SA-containing diet at doses of 0, 2, 3 and 4 g/kg for 12 days, then blood samples were collected on days 0, 3, 6, 9, and 12 to evaluate the total leucocyte count (TLC), phagocytic activity/index (PA/PI), respiratory burst, superoxide dismutase (SOD), lysozyme, alternative complement (ACH50) activity, total plasma protein (TPP), and immune genes expression (blood sample on day 6). The immunological parameters improved in response to the administered doses and period. Dietary SA enhanced total leucocyte count, phagocytic activity, respiratory burst, superoxide dismutase, lysozyme, and ACH50 activity, whereas the phagocytic index and total plasma protein were not significantly different. Furthermore, the mRNA levels of antioxidant-related gene (GPx), pro-inflammatory cytokines (TNF-α and IFN-Î³, except for IL-1β), and antimicrobial peptides (Hepcidin) were upregulated. Meanwhile, anti-inflammatory cytokines (IL-10 and TGF-β1) were downregulated. Supplementation SA diet at 2.0 g/kg as the lowest dose revealed the most effective effects on innate immune and immune genes expression. Dietary SA was a potential immunostimulant in red tilapia aquaculture.